Mitosis futures: the past is prologue - McIntosh, J. Richard (The American Society for Cell Biology, 2011)
The mechanisms by which cells organize and segregate their chromosomes have been under close scrutiny for years, and significant progress has been made in understanding how mitosis works. Modern cell biology has identified most of the molecules that underlie mitotic spindle function, but the ways in which they are organized and controlled to make an effective and accurate cellular machine are exciting subjects for future study.